Prediction of Stock Prices of IDX30-Indexed Companies using Dividend Policy, Profitability, and Firm Size - Wulandari, Rika Awalia; Ernawati, Nani; Prasetyo, Yoyok (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
This research aims to determine the influence of Dividend Policy, Profitability, and Firm Size in Predicting Stock Prices of IDX30-indexed companies simultaneously & partially. The data was obtained from the company's financial reports listed on the Indonesia Stock Exchange. The method used is a quantitative method. The sample was determined using a purposive sampling method on IDX30-indexed companies for the period 2018 to 2023. Based on this sampling, 16 companies were obtained as samples. The research findings show that Dividend Policy, Profitability, and Firm Size simultaneously influence Predicting Stock Prices, Dividend policy partially has no influence in predicting stock prices, while partially, both Profitability and Firm Size have an influence in Predicting Stock Prices. Keywords: Stock Price; Dividend Policy; Probability; Firm Size; IDX30